Pengaruh Motivasi, Kepuasan Kerja, dan Disiplin Kerja Terhadap Produktivitas Kerja Karyawan - Fauzi, Achmad; Muhammad Akbar, Fadel; Cahyaningtyas, Febrina; Adi Saputra, Lanang; Puspa Ningrum, Mega (Jurnal Ilmu Multidisiplin, 2023)
In an increasingly advanced era, an organization or company seeks to improve the performance of its employees to increase work productivity. Employee work productivity is an important factor in the success scale of a company's goals. To get maximum work productivity, it is necessary to have motivation, job satisfaction, and also work discipline that is embedded in each individual. When someone already has these three factors, maximum work productivity can be created. This article aims to find out how motivation, job satisfaction, and work discipline can affect work productivity. This research method uses quantitative methods and literature study by studying and understanding the concepts and relationships between the variables tested from previous journals. The results of the analysis in this article show that; 1) motivation affects work productivity. 2) job satisfaction affects work productivity. 3) work discipline affects work productivity. Based on the results of the analysis and discussion carried out in this article, it can be concluded that a) Motivation greatly influences work productivity. b) Job satisfaction greatly affects work productivity. c) Work discipline greatly affects work productivity.